Optimasi Waktu dan Biaya Proyek Gelanggang Olahraga Kalimantan Selatan dengan Metode Time Cost Trade-Off - Widiastuti, Endah; Sugiarti, Maesa Fitri; Yuliana, Candra; Karim, Abdul (Jurnal Manajemen Teknologi & Teknik Sipil, 2025)
Construction projects often face delays and cost overruns due to material delays, labor shortages, and adverse weather. In the Sports Building project in South Kalimantan, a 17-day delay beyond the planned 270-day schedule increased costs, risk of penalties, and threatened the contractor’s reputation and project sustainability. Therefore, accelerating completion is essential to reduce losses. Overtime on critical path activities is a common acceleration method but requires careful analysis since excessive overtime can reduce productivity and raise costs. This study aims to analyze alternatives for accelerating the duration of the construction of a sports arena in South Kalimantan using the Time Cost Trade-Off (TCTO) method. TCT) method is applied, focusing on adding 2, 3, and 4 hours of overtime per day on critical path tasks. The approach integrates actual project data, regulations, and productivity factors to develop effective acceleration strategies. Results show that adding 3 hours of overtime daily is the most efficient, reducing duration from 287 to 283 days and saving IDR 71,652,415.38. However, the 270-day target is not yet met, requiring further crashing. This paper presents only one crashing iteration as a practical simulation to demonstrate the method and potential outcomes. Future crashing will focus on tasks with the lowest cost slope while considering task dependencies.